Frequency and cutting height on Panicum maximum cv Gatton Panic - Schnellmann, Leandro Pablo; Verdoljak, Juan José O.; Bernardis, Aldo; Martínez-González, Juan Carlos; Castillo-Rodríguez, Sonia Patricia (Agronomía Mesoamericana, 2019)
Introduction. Livestock activity is developed in grazing as the main food resource. In central and northern Argentina new planted pastures are being used with higher biomass production and ability to keep forage quality longer. Objective. The objective of this study was to evaluate the production of dry matter (kg MS.ha-1), number of buds, and relation leaf:stem (H:T) of Panicum maximum cv. Gatton panic in two heights, three cutting frequencies, and two sampling periods. Materials and methods. The study was developed between April 2011 and May 2012. Two heights (0,15 and 0,30 m) and three cut-off frequencies (30, 45 and 90 d) were evaluated in two periods (90 and 180 d), using a completely randomized design with a factorial arrangement: 2 x 3 x 2. Results. Interaction between the variables (A) x height frequency (F) was found. The highest dry matter (MS) production was observed with the lowest height and the highest cutting frequency (0.15 m and 90 d) with 1877.2 kg MS.ha-1. For the number of buds the interaction A x F showed difference (p<0.05) for the combination of 0.30 m and 30 d, while the leaf - stem ratio (H:T) was affected by the interaction A x F. The best H:T ratio was obtained with the intermediate frequency and the higher height. Conclusion. The greatest MS production was obtained with the highest cutting frequency, in the shortest time, and with the lowest height. The highest number of buds was obtained with the lowest frequency, the shortest time, and the highest height; in addition the best H:T ratio was obtained with intermediate and low frequency, the shortest time, and the highest cutting heights.